GERD - still current problem of society, diagnosis, practical methods of management and treatment - Domańska, Anastazja; Babiak, Rafał; Bajak, Karolina; Czuchryta, Paulina; Gawęda, Agnieszka; Grabek, Agata; Rutkowska, Julia; Rzęsa-Tokarczyk, Żaneta; Skorek, Klaudia; Urbańczyk, Agnieszka (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Gastroesophageal reflux disease (GERD) is a very common digestive disease worldwide. About half of all adults will report symptoms of reflux at some point in their lives. The symptoms of the disease are non-specific, which is why doctors of many specializations face the problem both in doctor's offices and hospital rooms. GERD is a disorder with troublesome symptoms and complications resulting from the regurgitation of gastric contents into the esophagus, causing subjective symptoms and related complications, negatively affecting the quality of life. Symptoms negatively affect the quality of life of patients, lowering well-being, physical activity, and social functioning. Diagnosis is based in most cases on the observation of symptoms, which is why this paper presents the symptoms that should be taken into account when diagnosing patients. Therapeutic procedures, selection of the appropriate form of treatment: conservative, pharmacological and surgical, were discussed. Materials and methods: The review was based on the analysis of materials collected in the "Pubmed" database, books and other scientific articles. Summary: Gastroesophageal reflux disease is an important health problem because it is associated with impaired daily functioning and morbidity. Proper management of GERD symptoms can result in significant improvements in patients' well-being, including reduction in physical pain, increase in vitality, physical and social functioning, and improvement in emotional well-being. In some patients, only lifestyle modification and a change in habits are enough to reduce the occurrence of symptoms. First-line drugs are proton pump inhibitors. Endoscopic examination should be performed when pharmacological therapy is ineffective or in the event of alarm symptoms, i.e. dysphagia, weight loss, anemia, bleeding and recurrent vomiting. Surgical treatment is used as a last resort when pharmacological treatment fails.